Women Photographers and Female Identities: Annemarie Schwarzenbach, New Dandy and Lesbian Chic Icon. (2nd October 2018) - Muzzarelli, Federica
Abstract : This article explores how Swiss writer and photographer Annemarie Schwarzenbach (1908–1942), used photography, both as author and subject, to define a new identity and build a new visibility for women. It begins by exploring the shared poetics that drew women's artistic activities towards photography at the turn of the twentieth century. At that time, photography was a medium of choice for women seeking to reclaim their bodies and subtract them from the male gaze. It also provided women with an expression of identity, gender achievement and gendered negotiation. The article analyzes Schwarzenbach's photographic practice as a distinctive and complex case study within this context. A well-educated and wealthy young woman, Schwarzenbach embodied the image of the emancipated and independent new woman, both in her life and professional choices, bravely embarking on dangerous and difficult journeys, writing articles and taking photographs of far-away, diverse and suffering people. Nevertheless, it was only when she moved to the other side of the camera and became the subject of portraits taken by her female friends and partners that Schwarzenbach became the first-hand witness and icon of a new search for gender visibility. Her fashion choices and her own body expressed and codified a sophisticated lesbian chic style.